Political myth and historical reality in Nelson Mandela’s Long road to freedom - Jeff Peires (Contree, 2021)
P Bonner, “The headman, the regent and the ‘Long walk to freedom’”, Journal of Southern African Studies (2019); DS Yekela, “Unity and division: Aspects of the History of the AbaThembu chieftainship, c.1920 to c.1980” (PhD), University of Cape Town, 2011); DS Yekela, “AbaThembu politics: The era of the regents (1920-1954)”, Bulletin of the National Library of South Africa, 73(1), June 2019.